Interacting crack problems in 3D printed materials - Tan, Bernard Zhi Yang (Nanyang Technological University, 2023)
Perform elastic-plastic stress study on interface and sub-interface cracks in engineering materials where metal/alloys are fabricated using 3D printed technology through 2D finite element analysis as cladding of dissimilar metals/alloys may result in weak interfaces due to differences in their thermo-physical and chemical properties. Furthermore, the rapid melting and solidification of powders may lead to cracks along the interface or sub-interface of dissimilar metals. ANSYS Workbench 19.2 is used to conduct the study where simulations are carried out by creating 2D static structural models to obtain the stress intensity factors (SIF) for interface and sub-interface center cracks under a uniform tensile loading force. Furthermore, various factors such as type of interface, crack angles and Young's Modulus ratios will be considered for the simulation. A total of 7 cases are presented in this paper where the simulated SIF will be normalized against the theoretical SIF. It can be observed that as crack angle changes from 0 to 45 degree, the overall normalized SIF decreases for both flat and wavy interfaces. In addition, as Young's Modulus ratio increases at a crack angle of 45 degrees, both flat and wavy interfaces normalized SIF increases. However, the flat interface has a much lower normalized SIF as compared to wavy interface. Lastly, having a similar adjacent crack to the primary crack in a flat interface at 0 degree increases the overall normalized SIF. The data obtained from this project can serve as a guide for engineers and designers in the 3D printing industry to help them understand how SIF changes with various interfaces, EA/EB ratios and crack angles.